2010
DOI: 10.1073/pnas.1008861107
|View full text |Cite
|
Sign up to set email alerts
|

Combined agonist–antagonist genome-wide functional screening identifies broadly active antiviral microRNAs

Abstract: Although the functional parameters of microRNAs (miRNAs) have been explored in some depth, the roles of these molecules in viral infections remain elusive. Here we report a general method for global analysis of miRNA function that compares the significance of both overexpressing and inhibiting each mouse miRNA on the growth properties of different viruses. Our comparative analysis of representatives of all three herpesvirus subfamilies identified host miRNAs with broad anti-and proviral properties which extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 39 publications
(37 reference statements)
5
99
0
11
Order By: Relevance
“…We, therefore, conclude that the rescue of miR-27 levels in these experiments is not attributable to nonspecific effects of transfection or saturation of the RISC machinery by the siRNAs. The specificity of m169 function was confirmed by comparison with two other host miRNAs: miR-16, a miRNA that does not change in expression level in response to infection and miR-199a-3p, another miRNA that is down-regulated during infection (14). Neither miRNA displayed a significant change in expression level as a result of m169 knockdown (Fig.…”
Section: High-throughput Identification Of MCMV Rnas Associated Withmentioning
confidence: 56%
See 2 more Smart Citations
“…We, therefore, conclude that the rescue of miR-27 levels in these experiments is not attributable to nonspecific effects of transfection or saturation of the RISC machinery by the siRNAs. The specificity of m169 function was confirmed by comparison with two other host miRNAs: miR-16, a miRNA that does not change in expression level in response to infection and miR-199a-3p, another miRNA that is down-regulated during infection (14). Neither miRNA displayed a significant change in expression level as a result of m169 knockdown (Fig.…”
Section: High-throughput Identification Of MCMV Rnas Associated Withmentioning
confidence: 56%
“…All three miRNAs in this cluster target genes associated with cell proliferation, differentiation, and cancer and are predicted to function in a cooperative fashion (40). miR-24, in addition to miR-27, displays antiviral properties when overexpressed (14), and we show that the virus can be engineered to target miR-24 by mutation of 11 nt in the miRNA-binding site (Fig. 5C).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5 Recently, evidence has shown that miRNAs also have a role in viral infections, which include invoking an antiviral response; alternatively, the viruses themselves can encode miRNAs or regulate endogenous host miRNAs, which aid in the infection process. 6,7 There are currently 41000 putative miRNAs encoded in the human genome, and miRNAs are estimated to regulate up to 60% of protein-coding mammalian genes. 8 As the number of discovered miRNAs and their regulated targets continually increases, the biological importance of these small non-coding RNAs becomes more evident.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently this approach has been extended to miRNAs 20,21 , and is yet to be applied for the identification of miRNAs critical for infection by bacterial pathogens.…”
mentioning
confidence: 99%